Microtactile Cantilever Resonators for Characterizing Surface Deposits. (2015) - Wasisto, Hutomo Suryo; Dang, Ruochen; Doering, Lutz; Brand, Uwe; Peiner, Erwin
Abstract: Silicon cantilever resonators fabricated in a slender geometry are investigated for detecting characteristics of local elasticity of different surface deposits by monitoring changes of resonance frequency and quality factor ( Q -factor) corresponding to the physical properties of the materials. A full piezoresistive Wheatstone bridge (WB) for signal read-out and a wet-etched silicon tip for surface probing are integrated on the cantilever beam. From the material characterization, the harder the object surface, the larger the resonance frequency shift is while amplitude and Q -factor decrease. This sensor will be the key component of an adaptable form and roughness monitoring system for inline process control of machine tools for high-aspect-ratio microstructures.